Geospatial Environmental Influence on Forest Carbon Sequestration Potential of Tropical Forest Growth in Hainan Island, China - Lin, Meizhi; Song, Yanni; Lu, Di; Qiu, Zixuan (Frontiers in Environmental Science, 2022)
Tropical forests, although covering only 7% of the world’s land area, have great forest carbon sequestration capacity, accounting for 20% of the world’s forest carbon sink. However, the growth dynamics and forest carbon sink potential of tropical forests remain unclear. Hainan Island is going to be China’s forest carbon trading center. Therefore, accurately assessing the future forest carbon sink potential of Hainan Island’s tropical forest is crucial. In this study, 393 forest permanent sample plots in Hainan Island in 2003, 2008, 2013, and 2018 were selected as the research objects. The dynamic model of tropical forest growth with the geospatial environmental indicators was established based on the measured and most accurate annual diameter at breast height (DBH) growth factors. The DBH growth prediction’s bias ranged from 0.46 to 0.07 cm, RMSE ranged from 1.50 to 5.29 cm, bias% ranged from -2.96 to 0.55%, and RRMSE ranged from 12.18 to 34.30%. In addition, the geospatial environmental indicators of forest growth provide scientific guidance for future ecological protection and land evolution of Hainan Island. Based on DBH–tree height–volume, volume–biomass, and biomass–forest carbon storage relationships, forest carbon sequestration potential could be accurately evaluated by DBH growth. The results show that within the next 30 years, the forest carbon sequestration in Hainan Island will account for 1.8% of the total forest carbon sequestration in China, while the forest area will only account for 0.88% of the total forest area in China. It is roughly estimated that in the next 30 years, the total carbon sink of the tropical forest in Hainan Island will be 83.59 TgC. This study further proves that the annual increase in DBH can accurately assess the forest carbon sink potential of the forest. The forest carbon sink prediction based on the annual increase in DBH can provide data support and theoretical basis for forest carbon sink trading between forest farms and enterprises.